PARENTING GOES TO MUSEUM: KEGIATAN EDUKASI DI MUSEUM UNTUK ANAK DAN ORANG TUA - Desy Chrisnatalia; Andriyati Rahayu; Mira K Putri (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
The community service program targets parents and children who visit Museum Nasional. Visiting the museum should be a means of education for visitors, especially parents and children. Parents' limited knowledge of museum content and the ability to play with children can be an obstacle for parents in providing an educational and fun experience for children at the museum. The purpose of the Parenting Goes to Museum activity is to help parents by providing opportunities for children to learn about the museum's contents in a fun way and, at the same time, educate parents about parenting. The methods used in the parenting seminar are lectures and case studies, while on the museum tour, activities are problem-based learning, cooperative learning, and storytelling. The benefits of the activities obtained by parents and children are to provide opportunities for children to learn about the museum's collections in a fun way and develop parenting skills. The result of this community service is increasing parents' understanding of the children’s character and skills in parenting and the children's enthusiasm to explore the museum contents and their knowledge of the museum collections.   ---   Khalayak sasaran dari pengabdian masyarakat ini adalah orang tua dan anak yang mengunjungi Museum Nasional. Kunjungan ke museum dapat menjadi sarana edukasi bagi pengunjung terutama orang tua dan anak. Keterbatasan orang tua dalam hal pengetahuan isi museum dan kemampuan bermain dengan anak dapat menjadi hambatan bagi orang tua untuk dapat memberikan pengalaman yang edukatif dan menyenangkan bagi anak di museum. Tujuan kegiatan Parenting Goes to Museum yang adalah membantu orang tua untuk memberikan kesempatan bagi anak untuk mempelajari isi museum dengan cara yang menyenangkan dan sekaligus mengedukasi orang tua tentang cara pengasuhan. Metode yang digunakan pada kegiatan seminar parenting adalah ceramah dan studi kasus. Sementara pada kegiatan tur museum adalah problem based learning, cooperative learning, dan story telling. Manfaat kegiatan yang diperoleh orang tua dan anak adalah memberikan kesempatan kepada anak untuk belajar mengenai koleksi museum lewat cara yang menyenangkan dan juga mengembangkan kemampuan pengasuhan (parenting) orang tua. Hasil dari kegiatan pengabdian kepada masyarakat (PKM) ini yaitu bertambahnya pemahaman orang tua mengenai karakter anak dan keterampilan mereka dalam pengasuhan, serta antusiasme anak untuk mengeksplorasi isi museum sekaligus wawasan mereka mengenai koleksi museum.